MR-guided focused ultrasound thalamotomy for lithium-induced tremor: a case report and literature review - Kate Gelman; Joseph Melott; Vishal Thakur; Abdul R. Tarabishy; Abdul R. Tarabishy; Ana Brandt; Peter Konrad; Manish Ranjan; Adeel A. Memon (Frontiers in Neurology, 2024)
Drug-induced tremor is a common side effect of lithium with an occurrence of approximately 25% of patients. Cessation of the offending drug can be difficult, and many medical treatments for drug-induced tremor are ineffective. Deep brain stimulation (DBS) has been shown in a limited number of case reports to effectively reduce drug-induced tremor, however, which remains an invasive therapeutic option. MR-guided focused ultrasound (MRgFUS) thalamotomy is an FDA-approved non-invasive treatment for essential tremor (ET). To the best of our knowledge, MRgFUS thalamotomy has never been reported to treat drug-induced tremor. Here, we present a case of a left-handed 55-year-old man with a progressive, medically refractory lithium-induced tremor of the bilateral upper extremities. The patient underwent MRgFUS thalamotomy targeting the right ventral intermediate nucleus (VIM) of the thalamus to treat the left hand. There was almost complete resolution of his left-hand tremor immediately following MRgFUS. There were no side effects. The patient continues to show excellent tremor control at 90-day follow-up and remains free from side effects. This case demonstrates MRgFUS thalamotomy as a possible novel treatment option to treat drug-induced tremor.